2018
DOI: 10.1002/smtd.201800337
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Electrocatalytic N2 Reduction—Strategies to Tackle the Selectivity Challenge

Abstract: The industrial process used to reduce N 2 to NH 3 , typically the Haber-Bosch process, is energy-intensive and highly dependent on fossil fuels, a major source of greenhouse gas emissions causing undesirable climate change. Electrochemical reduction of N 2 to NH 3 using renewable energy is one attractive approach to address this problem. A major challenge for electrochemical nitrogen reduction reaction (NRR) is low catalytic activity, accompanied by ultralow selectivity. Current studies have made some breakthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
363
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 429 publications
(370 citation statements)
references
References 110 publications
7
363
0
Order By: Relevance
“…Interfaces 2019, 6,1901034 working electrode was prepared by dropping 28 µL of the prepared ink solution on the carbon substrate and dried naturally. Mater.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
See 3 more Smart Citations
“…Interfaces 2019, 6,1901034 working electrode was prepared by dropping 28 µL of the prepared ink solution on the carbon substrate and dried naturally. Mater.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
“…[2] This harsh condition is obviously energy consuming and accompanies a large amount of CO 2 output, bringing a serious global warming problem. [6] It has been extensively reported that heterogenous catalysts play vital roles in breaking or lowing the energy barrier required in the rate-determining step in electroreduction from N 2 to NH 3 , [7] which is the key in further improving N 2 reduction reaction (NRR) performances. [3][4][5] Among them, N 2 electroreduction is considered as the most promising and environmentally benign way because the electricity utilized during the catalysis can be produced by some renewable sources, such as solar and wind energy.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[3] In aqueous solution, the increase of the electric potential to enhance the activation of N 2 is an option of limited applicability as NRR under these conditions is largely inhibited by the competitive hydrogen evolution reaction (HER). [5] Until now, various promising catalysts have been investigated for electrochemical NRR, including metals, [6] metal oxides, [7] metal nitrides, [8] metal carbides, [9] metal complexes [10] and carbon-based materials. Theu ltimate requirement to such types of catalysts is to bind and polarize N 2 molecules in away that the electron density within the molecule is shifted to facilitate the reaction with protons and/or electrons.…”
mentioning
confidence: 99%